2007
DOI: 10.1074/jbc.m606455200
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Oligosaccharides on the Low Density Lipoprotein Receptor Homolog SorLA/LR11 Are Modified with Terminal GalNAc-4-SO4 in Kidney and Brain

Abstract: Sorting protein-related receptor (SorLA/LR11) is a highly conserved mosaic receptor that is expressed by cells in a number of different tissues including principal cells of the collecting ducts in the kidney and neurons in the central and peripheral nervous systems. SorLA/LR11 has features that indicate it serves as a sorting receptor shuttling between the plasma membrane, endosomes, and the Golgi. We have found that a fraction of SorLA/LR11 that is synthesized in the kidney and the brain bears N-linked oligos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…A possible mediator could be a transmembrane receptor of the Vps10-domain family, such as sortilin (21,59,60), sortilin-related receptor (SorLA) (16,61,62) or SorCS1 (63), which have been implicated in endosome-to-Golgi retrieval of receptors through retromer. SorLA is actually expressed in kidney (64). Indeed, SorLA could be immunoprecipitated from MDCK cells, and we confirmed that Vps35 can interact with SorLA independently of APP or BACE overexpression (our unpublished data).…”
Section: Figure 8: Bace Undergoes Apical-to-basolateral Transcytosis supporting
confidence: 80%
“…A possible mediator could be a transmembrane receptor of the Vps10-domain family, such as sortilin (21,59,60), sortilin-related receptor (SorLA) (16,61,62) or SorCS1 (63), which have been implicated in endosome-to-Golgi retrieval of receptors through retromer. SorLA is actually expressed in kidney (64). Indeed, SorLA could be immunoprecipitated from MDCK cells, and we confirmed that Vps35 can interact with SorLA independently of APP or BACE overexpression (our unpublished data).…”
Section: Figure 8: Bace Undergoes Apical-to-basolateral Transcytosis supporting
confidence: 80%
“…14 SorLA/LR11, highly expressed by neurons in the central and peripheral nervous systems, bears N-linked oligosaccharides modified with terminal ␤1,4 -linked GalNAc-4-SO 4 that can be synthesized by B4GALNT3 in CHO cells. 14 In Drosophila, ␤1,4-N-acetylgalactosaminyltransferase A (B4GALNTA) catalyzes synthesis of LacdiNAc on glycoconjugates. 15 Drosophila mutants deficient in B4GALNTA have defects in behavior and in the neuromuscular system.…”
Section: ␤14-n-acetylgalactosaminyltransferase III (B4galnt3)mentioning
confidence: 99%
“…There are a number of glycoproteins synthesized in other tissues that are also selectively modified with terminal GalNAc-4-SO 4 , for example, the LDL-receptor homolog SorLA/LR11 expressed in the kidney and the brain (48) and tenascin-R expressed in the brain (49). It is possible that additional differences between WT and GalNAc-4-ST1 -/-mice will be identified upon further examination; however, none of the other glycoproteins identified thus far as bearing structures terminating with SO 4 -4-GalNAcβ1,4GlcNAc would be expected to have an impact on steroid hormone production or reproduction.…”
Section: Figure 10mentioning
confidence: 99%